Recria tua vida, sempre : associativismo das Mulheres Coralinas da Cidade de Goiás (2017-2021) - Rodrigues, Rafael Ferreira (2022)
We seek with this dissertation the debate about the position that women occupy in our society, especially in the work environment. For this, we have drawn up a study about the process of associativism and inclusion of the guidelines of solidarity economy in the Association of Women Coralinas - ASCORALINAS (located in the Municipality of Goiás - Goiás). The years from 2017 to 2021 are the time frame of the research. The corpus of this work is based on an exploratory research where at first data on associativism and solidarity economy will be collected and at a second moment narrative interviews with some women associated with ASCORALINAS will be held. In addition, to endorse the narrative interview proposal we used the perspective of Clandinin and Connelly (2011) in line with the hearing proposal of subjects to understand the place of speech of the same, idea derived from the studies of Ribeiro (2017). Thus, we join the imbrications derived from the perspective of humanist geography in contact with the phenomenological method (SUESS, 2017; TUAN, 1982). As a theoretical basis, we used the gender debates of Scott (1994), Saffiotti (2013), Rubin (1975) among others; in addition to ideas on economics, solidarity pointed out by Singer (2002). A priori, we observed the presence of a social problem constituted by the relation of poverty to the female gender. In addition, we observe how the solidarity economy is a way out to another social space of inclusion and sharing experiences that is not necessarily directed only to the transfer of capital between people.